Making and breaking the grid : a graphic design layout workshop - Samara, Timothy; Ohio Library and Information Network (Beverly, MA : Rockport Publishers, 2023)
Making and Breaking the Grid: A Graphic Design Layout Workshop (Third Edition) is the ultimate resource for designers who want to understand the rules of the grid, so they can get better at breaking them
Includes bibliographical references and index
1 10
Keywords: Dummies (Bookselling); Grids (Typographic design); Layout (Printing)